Antiplaque Efficacy of a Novel Moringa oleifera Dentifrice: A Randomized Clinical Crossover Study - Duarte, Kimberly; Thomas, Biju; Varma, Sudhir Rama; Kamath, Vinayak; Shetty, Bhavya; Kuduruthullah, Syed; Nambiar, Manjusha (European Journal of Dentistry, 2022)
Objectives The use of herbal dentifrices has grown exponentially over the years. They are categorically referred to as ethnomedicines. Various agents have been tried with contradicting findings based on phytopharmacological analysis. Miswak is one agent which has been used over the years. A novel Moringa oleifera-based dentifrice has shown promising results in terms of its cytotoxicity, biocompatibility, and as a potent anti-inflammatory agent. Therefore, the present study aims to compare the efficacy of two commercially available miswak- and moringa-based herbal dentifrices on the reduction of plaque and gingivitis scores.Materials and Methods This randomized clinical crossover study included 20 subjects with mild to moderate gingivitis. The study was conducted over a total examination period of 20 days with a wash-out period of 2 weeks between the use of both the toothpastes. The plaque index and gingival index of the study subjects were recorded at the designated time intervals throughout the study period.Statistical Analysis The data collected were entered on Microsoft Excel, and statistical analysis using SPSS software (SPSS version 28, IBM Corp, Armonk, New York, United States) was done. The statistical test used was the Wilcoxon signed-rank test. Moreover, p ≤0.05 was considered significant.Results The results showed that the reduction in mean gingival index scores from baseline to day 3 was more statistically significant in the moringa-based dentifrice. Similarly, the plaque index scores showed statistically significant reduction following the use of the moringa-based dentifrice when compared with the miswak dentifrice. This study reveals that the moringa dentifrice is a safe and effective agent in reducing plaque accumulation and treating gingival inflammation.Conclusion The current study aims to provide an insight into the possible role of moringa dentifrice as a possible adjunctive oral hygiene aid.
Keywords: Moringa oleifera; miswak; Salvadora persica; gingival inflammation; dental plaque; herbal dentifrice